Eficiência dos gastos em segurança pública: um estudo dos estados do Nordeste Brasileiro - Torquato, José Edgardo (Universidade Federal Rural do Semi-Árido, 2019)
Violence has been rising dramatically in Brazil in recent years, which pressures governments to increase their investments in public security even in the face of scarcity of resources. In this context, this research aims to verify which states of the Northeast of Brazil used public security resources most efficiently. To verify the efficiency of the states, the non-parametric Data Envelopment Analysis (DEA) technique was used in 2017. The public safety expenditure was used as an input and the inverse number of homicides per 100 output. one thousand inhabitants. The results showed that the most efficient states in public security spending to reduce homicides were Maranhão and Piauí and the least efficient Sergipe and Alagoas.
Keywords: Segurança pública; Eficiência em segurança pública; Homicídio; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO